Flickering Sunrays: Capturing Divinity on Georgian Church Façades - Shneurson, Erga
Geometrical and floral ornaments such as the rosette can be found in Georgia as well as in the south and eastern areas neighboring it. Pagan societies used such decorative images for centuries. The subject has provoked discussion for over a century, generating diverse opinions, and it bears funerary context, symbolic function, concept of the divine, apostrophic function, and cosmic and solar connotations. The first source is from Mesopotamia, an abundance of Neo-Assyrian (9th – 7th centuries BCE). In the Caucasus, the rosette ornament, used in specific traditional images, is associated with the stable influence of religious beliefs and cults dating back to the Neolithic era. It was passed down from earlier local pagan beliefs into Christianity, being firmly established in this religion. Երկրաչափական և բուսական զարդատարրերը, որոնց թվին է պատկանում վարդյակը, կարելի է հանդիպել ինչպես Վրաստանում, այնպես էլ նրանից հարավ և արևելք գտնվող տարածքներում: Հեթանոսական միջավայրում նման դեկորատիվ տարրեր կիրառել են դարեր շարունակ: Թեման քննարկվում է ավելի քան մեկ դար՝ առաջ բերելով տարբեր կարծիքներ, որոնք անչվում են թաղման ծեսի հետ կամ ունեն խորհրդանշական, աստվածային և ապատրոպեիկ գործառույթ՝ կապվելով արևի և Տիեզերքի գաղափարների հետ: Վաղագույն օրինակները Միջագետքից են՝ հետասորական շրջանից (մ.թ.ա. 9-7-րդ դդ.): Հարավային Կովկասում վարդյակիզարդատարրը առկա է ավանդական դարձած պատկերներում և զուգորդվում է դեռ նեոլիթից եկած կրոնական հավատալիքների և ծեսերի հետ: Վաղ հեթանոսական հավատալիքներից այն թափանցում է քրիստոնեության մեջ և հիմնովին հաստատվում:
Keywords: Art history; Ornaments